2014
DOI: 10.2214/ajr.12.9642
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Radiation Savings of Partial Substitution of Ultrasound for CT in Appendicitis Evaluation: A National Projection

Abstract: An ultrasound-CT protocol for appendicitis evaluation offers potentially large savings over the standard CT-only protocol. There are moderate savings from using a less expensive imaging technique despite extra surgeries and large savings from radiation exposure avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 18 publications
0
41
0
3
Order By: Relevance
“…Lower values of sensitivity and specificity can be explained by the use of enteral contrast [32, 33, 3544]. However, the radiation exposure of abdominal CT is a concern particularly in children and during pregnancy.…”
Section: Pre-operative Carementioning
confidence: 99%
“…Lower values of sensitivity and specificity can be explained by the use of enteral contrast [32, 33, 3544]. However, the radiation exposure of abdominal CT is a concern particularly in children and during pregnancy.…”
Section: Pre-operative Carementioning
confidence: 99%
“…Although CT is reported to have a higher sensitivity than US, ongoing concerns have been raised regarding radiation exposure and increased costs associated with CT scans [12] . Projections estimated that a solid cancer will result at a rate of 25.8 to 33.9 cases per 10,000 abdominal CT scans in girls and, 13.1 to 14.8 cases per 10,000 abdominal CT scans in boys [23] . Furthermore, high costs and the need for sedation would limit the use of CT and MRI for diagnosing appendicitis in children.…”
Section: Resultsmentioning
confidence: 99%
“…They found that an ultrasound-CT protocol for appendicitis evaluation offers potentially large savings over the standard CT-only protocol [17]. In their analysis, the positive predictive value of ultrasound was 91 % compared with 92.5 % for CT scan (nonsignificant difference).…”
Section: Discussionmentioning
confidence: 97%